2022
DOI: 10.1186/s12933-022-01646-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations of circulating thrombospondin-2 level with heart failure hospitalization, left ventricular remodeling and diastolic function in type 2 diabetes

Abstract: Background Circulating thrombospondin-2 (TSP2) levels were associated with the development of heart failure (HF) in recent studies. However, these studies included only a minority of patients with type 2 diabetes, which is associated with an increased HF risk. As hyperglycemia induces TSP2 expression and its tissue expression increases in type 2 diabetes, we investigated the prospective association of circulating TSP2 with incident HF hospitalization (HHF), and its associations with longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In addition to hepatic fibrosis, ECM remodelling is also a key pathogenic event in other diabetic complications, such as diabetic kidney disease and heart failure (HF) 35–37 . Recently, we demonstrated that baseline circulating TSP2 was associated with rapid kidney function decline and incident HF hospitalization in T2D patients 38,39 . Our current findings therefore provided further clinical support to develop circulating TSP2 as a useful biomarker for all these fibrotic complications that commonly occur in T2D patients.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to hepatic fibrosis, ECM remodelling is also a key pathogenic event in other diabetic complications, such as diabetic kidney disease and heart failure (HF) 35–37 . Recently, we demonstrated that baseline circulating TSP2 was associated with rapid kidney function decline and incident HF hospitalization in T2D patients 38,39 . Our current findings therefore provided further clinical support to develop circulating TSP2 as a useful biomarker for all these fibrotic complications that commonly occur in T2D patients.…”
Section: Discussionsupporting
confidence: 56%
“…[35][36][37] Recently, we demonstrated that baseline circulating TSP2 was associated with rapid kidney function decline and incident HF hospitalization in T2D patients. 38,39 Our current findings therefore provided further clinical support to develop circulating TSP2 as a useful biomarker for all these fibrotic complications that commonly occur in T2D patients.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, top proteins related to pollution exposures (specifically PM 2.5 ) were in pathways of DNA damage repair (APEX1 [DNA-(apurinic or apyrimidinic site) lyase], 46 a main AP endonuclease; RECQL [RecQ like helicase] 47 ), mitochondrial metabolism (COQ9 [coenzyme Q9] 48 ), proteins at the lung-pollutant interface (SP-D [pulmonary surfactant-associated protein D] 49 ), inflammation, and transcriptional/translational processing (ribosomal and nuclear proteins). Both unbiased analysis and per-protein review did not suggest a predominant pathway signature of the social vulnerability proteome but did include several mediators previously implicated in CMD pathogenesis (GDF15 [growth/differentiation factor], 50 RARRES2 [retinoic acid receptor responder 2], 51 and THBS2 [thrombospondin-2], 52 among them). Molecular pathways implicated by temperature appeared analogous to the pollution and built environmental proteome, likely reflecting some correlation between measures of temperature, elements of pollution, and built structures (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Although a deep survey per-protein exposition is out of scope for this report, we did note overlap across environmental exposures in pathways relevant to CMD that were consistent with the pathway analysis. For example, proteins related to the built environment included downstream mediators of broad fibrosis and immune signaling pathways, including 51 and THBS2 [thrombospondin-2], 52 among them). Molecular pathways implicated by temperature appeared analogous to the pollution and built environmental proteome, likely reflecting some correlation between measures of temperature, elements of pollution, and built structures (Figure 1B).…”
Section: Human Proteome-envirome Relations Implicate Broad Pathways R...mentioning
confidence: 99%
“…subclinical CHD [ 36 ]. Furthermore, we identified THBS2 as a marker of incident CHD, which is a matricellular protein facilitating cell-matrix interactions, that was positively associated with both incident heart failure (HF) hospitalization and deterioration in diastolic function in a recent study [ 37 ]. TGF-alpha, which directly activates the transcription factor NF-κB through the epidermal growth factor receptor pathway, was previously found to be associated with higher cardiovascular mortality in patients with chronic CHD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%